Analysis and Research of Muti-gear and Rack Drive of SAC - Dai Haolin; Fu Jinqi; Zhao Hao; Du Jun; Zhu Changjin (Jixie chuandong)
The influence of different mounting distance of driving device of side-arm charger（ SAC） on the engaging force of driving gear and rack and moving stability of SAC is analyzed. By using the theoretical calculation and ADAMS software,the analysis and study of the dynamic behavior of driving gear and rack of SAC in the process of movement are carried out. The results has provide a reference for SAC driving device design.